The Challenges of Symmetrical Dialogue: Reflections on Collaborative Research in Northeast Brazil - Bollettin, Paride; El-Hani, Charbel N.; Ludwig, David (Ethnobiology Letters, 2023)
This article explores ways to promote symmetrical dialogue among knowledge-practices of artisanal fishing communities, primary education teachers, and academic researchers in the state of Bahia, Brazil. We describe multiple engagements in an inter- and transdisciplinary project that integrates research, educational, and conservation activities in two communities living in an estuarine ecosystem. Most community members dedicate their efforts to fishing activities, harboring wide knowledge about local biocultural diversity. The project promotes collaborative inclusion of local expertise and knowledge in school activities, while also striving for the inhabitants’ inclusion in the planning of protected areas. The collaboration aims at symmetrical dialogues between researchers and communities that support self-determination in local school education and biodiversity conservation. Challenges to such symmetrization, including disagreements and tensions among diverse actors, not only appear in encounters of local and academic knowledge, but also within the interdisciplinary project involving natural sciences, social sciences, and philosophy.